2013
DOI: 10.1038/embor.2013.152
|View full text |Cite
|
Sign up to set email alerts
|

Foxo‐mediated Bim transcription is dispensable for the apoptosis of hematopoietic cells that is mediated by this BH3‐only protein

Abstract: The BH3-only protein Bim is a critical initiator of apoptosis in hematopoietic cells. Bim is upregulated in response to growth factor withdrawal and in vitro studies have implicated the transcription factor Foxo3a as a critical inducer. To test the importance of this regulation in vivo, we generated mice with mutated Foxo-binding sites within the Bim promoters (Bim DFoxo/DFoxo ). Contrary to Bimdeficient mice, Bim DFoxo/DFoxo mice had a normal hematopoietic system. Moreover, cytokine-dependent haematopoietic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 28 publications
3
25
0
Order By: Relevance
“…46 PUMA as well as BIM expression were reported to be induced by the transcription factor FOXO3a in response to cytokine withdrawal. [47][48][49] However, mutation of all known FOXO transcription factorbinding sites in the Bim gene had no impact on haematopoietic cell homeostasis and apoptosis, 50 indicating that this mode of induction may not be critical for BIM activation. In response to ER stress, BIM expression can be transcriptionally induced by CHOP.…”
Section: The Bcl-2-regulated Apoptotic Pathwaymentioning
confidence: 99%
“…46 PUMA as well as BIM expression were reported to be induced by the transcription factor FOXO3a in response to cytokine withdrawal. [47][48][49] However, mutation of all known FOXO transcription factorbinding sites in the Bim gene had no impact on haematopoietic cell homeostasis and apoptosis, 50 indicating that this mode of induction may not be critical for BIM activation. In response to ER stress, BIM expression can be transcriptionally induced by CHOP.…”
Section: The Bcl-2-regulated Apoptotic Pathwaymentioning
confidence: 99%
“…A number of mechanisms of regulation of these Bcl-2-proteins have also been proposed, such as phosphorylation and translocation, but the only clearly established mechanism of regulation of the activity of Bcl-2-proteins is through the regulation of their levels [13]. Thus, the withdrawal of IL-2 causes some upregulation of Bim and Puma through the activity of the transcription factor Foxo3a [9], although this does not seem to be relevant for Bim-induced apoptosis [14]. Mcl-1 protein levels can be regulated through IL-7 signals [5], while Noxa is upregulated under conditions of glucose shortage [11].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike Foxo3, knockdown of Foxo1 in endothelial cells did not affect levels of Bim, 27 and while expression of constitutively active FOXO4 could induce Bim expression and apoptosis in endothelial progenitor cells, it did not induce death in mature endothelial cells. 50 Taken in combination with recent findings in hematopoietic cells, 34 it would appear that direct FOXO binding to the Bim promoter is not critical for BIM-dependent apoptosis in general. However, our analysis of endothelial apoptosis was by no means exhaustive, and we cannot exclude the possibility that …”
Section: Discussionmentioning
confidence: 78%
“…To establish whether BIM-dependent hyaloid regression was due to the redundant activity of FOXO transcription factors, we assessed hyaloid vessel regression in mice in which the four FOXO-binding sites located between positions À 625 -þ 2509 of the Bim transcriptional start site had been mutated (Bim DFoxo ). 34 Mutation of these four binding sites prevents transcriptional induction of Bim by constitutively active FOXO3. 34 Quantitative assessment at P8 showed that hyaloid regression proceeded normally in Bim DFoxo/DFoxo mice (Figure 4d).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation